A Double-Edged Sword Role of Cytokines in Prostate Cancer Immunotherapy - Mao, Chenyu; Ding, Yongfeng; Xu, Nong (Frontiers in Oncology, 2021)
Prostate cancer (PC) is one of the most common malignancies among men and is the second leading cause of cancer death. PC immunotherapy has taken relatively successful steps in recent years, and these treatments are still being developed and tested. Evidence suggests that immunotherapy using cytokines as essential mediators in the immune system may help treat cancer. It has been shown that cytokines play an important role in anti-tumor defense. On the other hand, other cytokines can also favor the tumor and suppress anti-tumor responses. Moreover, the dose of cytokine in cancer cytokine-based immunotherapy, as well as the side effects of high doses, can also affect the outcomes of treatment. Cytokines can also be determinative in the outcome of other immunotherapy methods used in PC. In this review, the role of cytokines in the pathogenesis of cancer and their impacts on the main types of immunotherapies in the treatment of PC are discussed.